Easy and effective test to evaluate tear-film stability for self-diagnosis of dry eye syndrome: blinking tolerance time (BTT) - Hwang, Hyung Bin (BMC Ophthalmol, 2020)
BACKGROUND: The tear film breakup time (tBUT) is a clinical evaluation of evaporative dry eye disease assessed by instilling topical fluorescein into the eyes. In the present study, we introduce a new diagnostic test, blinking tolerance time (BTT), for self-evaluation of tear-film stability. We compared the results with the tBUT and validated the BTT test for self-assessment of tear film instability. METHODS: This was a prospective controlled study involving 212 eyes of 106 participants 20–79 years of age. A total of 114 eyes of 57 dry eye patients and 98 eyes of 49 healthy subjects were included in the study. All patients and subjects were administered the following tests to diagnose dry eye disease: Ocular Surface Disease Index, BTT, tBUT, slit-lamp examination, corneal stain score, and Schirmer I test (without anesthesia). Patients and subjects were instructed not to blink for as long possible after reset blinking. The time interval between the reset blink and the next blink was measured. The mean of 3 tBUT values in both the right and left eyes was defined as tBUT(BE). Correlations between the BTT and tBUT(BE) were also evaluated. To evaluate the diagnostic efficacy of the BTT and tBUT tests, receiver operating characteristic (ROC) curves were generated to obtain a cutoff score, and the sensitivities of the tests against the specificity at all possible thresholds were plotted. RESULTS: Spearman’s correlation analysis revealed a significant weakly positive correlation between BTT and tBUT(BE) (r = 0.447; p = 0.000). The intraclass correlation coefficient (ICC) of the tBUT was 0.679 (95% confidence interval [CI]: 0.575–0.765) and the ICC of the BTT was 0.904 (95% CI: 0.867–0.932). The area under the ROC curve did not significantly differ between the tBUT(BE) (0.678) and BTT (0.628, p = 0.641). When the cutoff value of the BTT test was set to 8.1 s, the sensitivity was 63.3% and the specificity was 56.1%. CONCLUSION: The BTT test is a simple, inexpensive, and effective method for self-diagnosing dry eye that can also be used in the clinical setting.